Vehicle-routing optimization for municipal solid waste collection using genetic algorithm: the case of southern Nablus city = Optymalizacja zbiórki odpadów komunalnych z wykorzystaniem algorytmu genetycznego: studium przypadku - miasto Nablus Palestyna - Assaf, Ramiz; Saleh, Yahya (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Municipalities are responsible for solid waste collection for environmental, social and economic purposes. Practices of municipalities should be effective and efficient, with the objectives of reducing the total incurred costs in the solid waste collection network concurrently achieving the highest service level.
Keywords: solid waste collection; Vehicle Routing Problem; genetic algorithms; integer program; zbieranie odpadów; algorytm genetyczny